Phosphorylation in Crested Wheatgrass Seeds at Low Water Potentials - Wilson, A. M. (1968)
Crested wheatgrass seeds [Agropyron desertorum (Fisch. ex Link) Schult.] were tested for their ability to carry on phosphorylation reactions at low water potentials. Seeds were treated with (32)P labeled sodium phosphate and incubated in air having different controlled relative humidities. Ion exchange chromatography and radioassay of phosphate esters indicated that some phosphorylation occurred at a water potential of −880 atmospheres. Seeds did not incorporate (32)P in nicotinamide adenine dinucleotide, adenosine triphosphate, and uridine diphosphate hexose until they were moistened to a water potential of −130 atmospheres.